7 = 3a + 6 should be your answer
Answer:
?
Step-by-step explanation:
<h3>
Answer: y = x+1</h3>
===================================================
Explanation:
f(x) = x^3 - 2x + 3
f ' (x) = 3x^2 - 2 ..... apply the power rule
f ' (1) = 3(1)^2 - 2 ... plug in x coordinate of given point
f ' (1) = 1
If x = 1 is plugged into the derivative function, then we get the output 1. This means the slope of the tangent line at (1,2) is m = 1. It's just a coincidence that the x input value is the same as the slope m value.
Now apply point slope form to find the equation of the tangent line
y - y1 = m(x - x1)
y - 2 = 1(x - 1)
y - 2 = x - 1
y = x - 1 + 2
y = x + 1 is the equation of the tangent line.
The graph is shown below. I used GeoGebra to make the graph.
Answer:
5/6
Step-by-step explanation:
Multiply both sides of equation by 10/3.
d = 1/4 × 10/3
d = 10/12 = 5/6
Answer:x=8
Step-by-step explanation:
You have to subtract 12 to 4
So x=8